The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.21203/rs.3.rs-75462/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Child maltreatment, cognitive functions and the mediating role of mental health problems among maltreated children and adolescents in Uganda

Abstract: Background: Child maltreatment poses high risks to the mental health and cognitive functioning of children not only in childhood but also in later life. However, it remains unclear whether child maltreatment is directly associated with impaired cognitive functioning or whether this link is mediated by mental health problems. Our study aimed at examining this research question among children and adolescents in Uganda. Methods: A sample of 232 school-going children and adolescents with a mean age of 14.03 (SD = … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
(103 reference statements)
0
1
0
Order By: Relevance
“…At local level, Domestic legislations in Uganda include: The National Child Policy, 2020; The Children 's Act, 2006; The Constitution of Uganda, 1995;The Local Government Act, 1997;The National Council for Children Act, 1996;The Trafficking in Persons Act, 2008;The Employment Act, 1977;The Births and Registration Act, 1973;The Land Act, 1997;The Child Labour Policy, 2006;The Orphans and Vulnerable Children Policy, 2004. Child maltreatment may include emotional, physical, and sexual violence as well as neglect. In a study on child maltreatment, cognitive functions and the mediating role of mental health problems among maltreated children and adolescents in Uganda, the researchers reported that children with experiences of child maltreatment performed poorly on tasks of working memory, attention, episodic memory and executive functions (Ainamani et al, 2021). Similarly DeBoer and colleagues reported that child maltreatment resulted into traumatic stress, depression, fear, and low self-esteem among victims (DeBoer & Seaver, 2019;Galagali, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…At local level, Domestic legislations in Uganda include: The National Child Policy, 2020; The Children 's Act, 2006; The Constitution of Uganda, 1995;The Local Government Act, 1997;The National Council for Children Act, 1996;The Trafficking in Persons Act, 2008;The Employment Act, 1977;The Births and Registration Act, 1973;The Land Act, 1997;The Child Labour Policy, 2006;The Orphans and Vulnerable Children Policy, 2004. Child maltreatment may include emotional, physical, and sexual violence as well as neglect. In a study on child maltreatment, cognitive functions and the mediating role of mental health problems among maltreated children and adolescents in Uganda, the researchers reported that children with experiences of child maltreatment performed poorly on tasks of working memory, attention, episodic memory and executive functions (Ainamani et al, 2021). Similarly DeBoer and colleagues reported that child maltreatment resulted into traumatic stress, depression, fear, and low self-esteem among victims (DeBoer & Seaver, 2019;Galagali, 2020).…”
Section: Introductionmentioning
confidence: 99%